School activities in health education and their impact on parents (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
There is little empirical evidence establishing the value of schoolhouse education of children and the repercussions on their families; a quantitative analysis of instructional intervention in health and its reflection on the family permits quantification of its effectiveness outside of the school setting. To this end, we utilized instruction on head lice in schoolchildren was conducted. A randomized sample of those responsible for students enrolled from the third to fifth grade, from two public schools who had taken an instructional module on pediculosis, were invited to respond to a questionnaire that aimed to ascertain their opinions on the instruction and what its impact was on their family. The variables were assessed by univariat analysis. Of 155 total respondents, 89.9% were the parents of the students. The students that had infestation, in turn, had greater capacity to influence the family on measures against lice. The majority of those responsible supported the instruction and reported being satisfied with the school for having addressed the theme. When the subject pertains to the reality of the students, the school-family link is strengthened. Instruction on pediculosis in school helps bridge the gap between the theoretical and the practical, a harmonization required in health education.